(untitled) (Historia, 2021)
Wirz' doctoral thesis on the history of women mountaineering in Switzerland between 1840 and 1940, goes beyond the mere academic informative - it dares to be an entertaining read too. While showing with great aplomb that the depiction of the Alps and of "conquering" them always implies a meta-discourse on dominance and othering, Wirz does not fall into the trap of re-hashing truisms about the so-called battle between the sexes.